Efektifitas Daun Kersen (Muntinga calabura L.) dalam Menurunkan Jumlah Bakteri dalam Susu dan Peradangan Pada Ambing Sapi Perah - Dyah Rumaniar Prasetyanti; Christina Budiarti; Dian Wahyu Harjanti (Fakultas Peternakan Universitas Jambi, 2016)
Indonesia has a huge potency of medical plants. However the utilization for livestock health and production are limited. A research was conducted to determine the efficacy of Muntinga calabura L. leaves to reduce bacterial population in milk using postmilking teat dip method with Muntinga calabura leaves solution in the concentration of 20%, 30% and 40%. The degree of mammary inflammation was observed using California Mastitis Test (CMT). The result showed that the bacterial population in milk were reduced by 79.36%, 71.12% and 73.84% with Muntinga calabura solution (in the concentration of 20%, 30% and 40%, respectively). The bacterial counts among the treatment groups were similar (P>0.05). Compared with synthetic antiseptic povidone iodine, the reduction of bacterial population in milk did not differ (P>0.05) with the Muntinga calabura groups. Postmilking teat dip using povidone iodine reduced bacterial population in milk by 79.36%. Moreover, the CMT reading were decrease by 39.96%, 34.76% and 31.15% in the Muntinga calabura groups (solution concentration of 20%, 30% and 40% respectively). The CMT results of Muntinga calabura groups were comparable (P>0.05) with iodine group (35.16%). In conclusion, our results indicated that Muntinga calabura leaf can be use as an alternative teat dip antiseptic to reduce bacterial population in milk and it can be use for sub clinical mastitis treatment.